Quechua phrasebook & dictionary - Myers, Jenna (Lonely Planet, 2019)
Lonely Planet's Quechua Phrasebook is your passport to culturally enriching travels with the most relevant and useful Quechua phrases and vocabulary for all your travel needs. Ask for hiking directions, learn about local culture and shop at markets with confidence- all with your trusted travel companion.